Analisis Ketidaklengkapan Rekam Medis Pasien Rawat Inap di Rumah Sakit Dharma Kerti Tabanan - Wirajaya, Made Karma Maha; Dewi, Ni Made Umi Kartika (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2019)
One parameter to determine the quality of health services in hospitals are information from medical records that is good and complete. Based on observations, there are some pieces of missing medical records and there are still some incomplete medical records. This study aim to analysis the complete inpatients medical records at Dharma Kerti Tabanan Hospital. This study was descriptive study conducted at the Dharma Kerti Tabanan Hospital. This study use 232 inpatients medical records and use systematic random sampling. Based on the results of the analysis found that in terms of completeness of identification, classified as incomplete (99.14%). In terms of the completeness of recording, it is classified as incomplete (59.48%). In terms of completeness of reporting, it is classified as complete (61.64%) and completeness of authentication, classified as complete, (74.14%). Overall, the medical records of inpatients are classified as incomplete at 85.78%. Dharma Kerti Tabanan Hospital needs to pay closer attention to the contents of the medical record and coordinate with doctors or nurses to keep filling in complete medical records of inpatients. In addition, medical record storage should be provided better in order to prevent the loss of important sheets in medical record documents.